Effect of K2O on the lubrication and heat transfer performance of continuous casting mold flux - Liguang ZHU; Chaofei GUO; Zhihong GUO; Baochen HAN; Xianhui WANG; Tianwei XIE; Hairui ZHAO; Lin CHENG (Journal of Hebei University of Science and Technology)
To improve the lubrication performance and heat transfer control capability of continuous casting mold flux, the effects of K2O on its properties were systematically investigated by using a rotary viscometer, infrared emissivity technique (IET), infrared spectrometer, Raman spectrometer, and X-ray diffractometer (XRD). The results indicate that when the K2O content increases from 0 to 6 wt.%, the viscosity of the mold flux (at 1 300 ℃) initially decreases and then increases, and reaching its minimum value at 2 wt.% K2O, along with the lowest transition temperature. Microstructural analysis reveals that the proportions of simple structural units (Q0 and Q1) in the molten slag firstly increase and then decrease, while complex structural units (Al-O-Al and Si-O-Al) exhibit the opposite trend. This leads to an initial reduction followed by an increase in the overall structural complexity and polymerization degree of the slag. Furthermore, increasing K2O content promotes the precipitation of the Bredigite phase (Ca7Mg(SiO4)4) while suppressing the formation of the Cuspidine phase (Ca4Si2F2O7), resulting in a gradual decline in the heat flux density of the mold flux. Comprehensive analysis demonstrates that the optimal K2O content of 2 wt.% significantly enhances both lubrication performance and heat transfer regulation of the mold flux, which provides theoretical reference for optimizing continuous casting processes.